2008
DOI: 10.5032/jae.2008.01121
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Doctoral-Level Content in Agricultural Education: Viewpoints of Engaged Scholars in the United States

Abstract: In this study, the researchers used a classical Delphi method to reexamine the conceptual framework, definition, and knowledge base of the field. Seventeen engaged scholars, each representing the expert agricultural education community, reached consensus on defining the field of study, 10 knowledge domains, and 67 knowledge objects. The Delphi panel agreed, "Agricultural education-2010, as a field of study, integrates social and behavioral sciences with the natural and applied science of agriculture, renewable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…The classic Delphi study has four phases which serve to take the broad quantity of data provided by panelists in the early rounds and gradually pare it down to a concise summary in the final round (Linstone & Turoff, 2002). This study emulated the design used by Shinn, Briers, and Baker (2008). It had four multi-segmented rounds that were conducted using SurveyMonkey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic Delphi study has four phases which serve to take the broad quantity of data provided by panelists in the early rounds and gradually pare it down to a concise summary in the final round (Linstone & Turoff, 2002). This study emulated the design used by Shinn, Briers, and Baker (2008). It had four multi-segmented rounds that were conducted using SurveyMonkey.…”
Section: Methodsmentioning
confidence: 99%
“…The development of a vision for the year 2015 was designed to orient the panelists' thinking toward the future, thereby minimizing the threat of backward thinking identified by Athey and Orth (1999). A similar approach to visioning and competency identification was used by the North Carolina Cooperative Extension Service's Blue Ribbon Commission on Staff Development and Training (1999), Shinn et al (2008), and Shinn, Wingenbach, Briers, Lindner, and Baker (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Few standards exist for what should be included in a master's or doctoral program for leadership educators. In their seminal Delphi study to identify the knowledge base needed for doctoral education, Shinn, Briers, and Baker () identified eleven competencies: planning and needs assessment; curriculum development; learning theory; instructional design; delivery strategies; evaluation; research methods and tools; scholarship and writing; history, philosophy, and ethics; and contextual applications, culture, and diversity. In another Delphi study, Hyatt and Williams () identified roles and competencies of doctoral faculty who teach in leadership programs.…”
Section: Graduate Faculty Roles In Preparing Leadership Educatorsmentioning
confidence: 99%
“…Several studies recommend that future leadership educators have a strong foundation in aspects of leadership learning as well as instructional design and delivery (Hyatt & Williams, ; Shinn et al., ). As Guthrie and Jenkins () discuss in the leadership learning framework, when learning is framed as an outcome it creates opportunities for intentional approaches to teaching.…”
Section: Preparing Emerging Teachers Of Leadershipmentioning
confidence: 99%
“…2 http://www.uel.br/projetos/iccal/ Using "Ethics and Applied Linguistics", we localized two studies (viz., Goldacre, Bolt, & Lambiris, 2013;Kim, 2008). Using "Ethics and Critical and Applied Linguistics", we found 15 researches (viz., Abrams, 2005;Angel & Simpson, 2007;Arnett & Mady, 2010;Davari, Iranmehr, & Erafni, 2012;Derrington & Larsen, 2009;Goldacre, Bolt, & Lambiris, 2013;Guardado, 2012;Jin, 2011;Mossman, 2012;Sánchez, 2007;Shinn, Briers, & Baker, 2008;Swain & Lapkin, 2011;Welch, Hieb, & Graham, 2015;Wernicke, 2010;Zhao, 2014). The term "Ethics and emancipatory" had just one paper (viz., Scalia & Scalia, 2011).…”
Section: Methodological Procedures and Data's Characteristicsmentioning
confidence: 99%